Preliminary evaluation of CAES system concept with partial oxidation gas turbine technology. (15th September 2019) - Wróbel, Marlena; Kalina, Jacek
Abstract: This paper presents the concept of compressed air energy storage (CAES) system with Partial Oxidation Gas Turbine (POGT) technology. In this type of turbine fuel is oxidized with an excess air coefficient λ of less than 1.0. Therefore, a given value of the turbine inlet temperature (TIT) can be reached at significantly lower air consumption. POGT products are electric power and combustible process gas that can be utilised in various ways. In this paper there is assumed a bottoming process, which consists of low pressure combustion and a secondary turboexpander. The system is considered to be functioning in power-to-power mode. However, POGT creates also other opportunities that can help improve flexibility of energy market. As the paper presents an initial study of possibilities the proposed system has been compared against the existing plant in Huntorf (Germany). In this way main differences as well as advantages and limitations of the proposed solution are compared against the existing conventional first generation CAES facility. The study is focused mainly on key thermodynamic parameters and potential performance improvement of the CAES process. The results revealed considerable round-trip efficiency gains. Highlights: CAES system with partial oxidation gas turbine (POGT) is proposed. Performance of the system has been compared against the Huntorf CAES plant. Round-trip energy efficiency gains are demonstrated. Opportunities for system integration of CAES system with POGT are outlined.